Design and implementation of the performance arts enhanced three-stage instructional model. Issue 3 (4th May 2022) - Oladipo, Adenike Julianah; Akhigbe, Jeremiah Nosakhare
Abstract: There is a knowledge gap in best practices for incorporating performance arts into science instructions. The study focused on the design and implementation of the Performance Arts Enhanced 3-Stage Instructional Model (PAEIM), which incorporated drama, dance and music. The PAEIM was implemented in mixed factorial quasi-experimental research during the learning of the ecology unit in the secondary school biology curriculum. Empirical findings from the study exemplified PAEIM as an effective instructional model that significantly enhanced the conceptual understanding of ecology and impacted students' self-determination and intrinsic motivation. The reports of the findings also indicated that PAEIM enhanced the students' learning outcomes regardless of their gender. The result from the multivariate analysis revealed a significant main effect of treatment on combined motivation and the conceptual understanding of ecology. The study thereafter provided recommendations for scalability in the implementation of PAEIM in future research.